Judah and Tamar: A missiological study of Genesis 38 in its redemptive-historical context - Barend (Bob) Wielenga (In die Skriflig)
In this article, Genesis 38 was researched with missiological interests in mind. Using the redemptive-historical reading strategy, the importance of the Bible, and especially of the Old Testament, for missions has been stressed, based on the analysis of Genesis 38. Attention was paid to the literary framework in which Genesis 38 appears, constructed around the 11 toledōth statements in Genesis. The results of this literary analysis were used for a thematic reading of Genesis 38, focusing on some central issues such as the theocentric character of redemptive history, the interconnectedness of the editorial and divine communicative intentions with the inclusion of Genesis 38 in the established literary tradition of Genesis 37–50, the significance of the three-fold promise of God to Abraham (Gn 12:1–3)1 for the interpretation of Genesis 38, and the impact of Judah and Tamar on Israel’s ancient history. Next, the redemptive-historical analysed text was missionally re-read to show the present Christian community of faith how important this narrative could be for its missiological reflections and missional praxis, with attention paid to three central missiological issues: the missio Dei, the missiones ecclesiae, and corporate worship for missions.